Environmental hazards and stress: evidence from the Texas City Stress and Health Study. Issue 10 (11th March 2009) - Peek, M K; Cutchin, M P; Freeman, D; Stowe, R P; Goodwin, J S
Abstract : Background: Substantial research has suggested that exposure to environmental health hazards, such as polluting industrial activity, has deleterious effects on psychological and physiological well-being. However, one gap in the existing literature is comparative analysis of objective and subjective exposure's relative association with various measurable outcomes of exposure. Methods: These relationships were explored within a community sample of 2604 respondents living near a large petrochemical complex in Texas City, Texas, USA. Objective exposure was investigated using distance of residence from a cluster of petrochemical plants and subjective exposure using residents' concern about potential health effects from those plants. Regression models were then used to examine how each type of exposure predicts perceived stress, physiological markers of stress and perceived health. Results: Results suggest that objective exposure was associated primarily with markers of physiological stress (interleukin-6 and viral reactivation), and subjective exposure (concern about petrochemical health risk) was associated with variables assessing perceived health. Conclusions: From the analysis, it can be inferred that, in the context of an environmental hazard of this type, subjective exposure may be at least as important a predictor of poor health outcomes as objective exposure.